The Mechanism of Safety Culture Construction in Chinese Universities Based on POI Data and Gravity Model. (7th October 2022) - Zhao, Wu; Zhou, Zhe; Jiang, Haibo
Abstract : Safety culture includes concept culture, system culture, behavior culture, and material culture. With the development of social economy, the importance of safety culture has been recognized by the whole society. Campus security is not only related to the common interests of the campus teachers and students but also related to the fundamental interests of each individual in the campus. In order to build a "harmonious society, " building a "harmonious campus" is an important work. Strengthening the construction of safety culture in colleges and universities is not only the objective need of building a harmonious society, promoting the reform and development of colleges and universities, and running a university with the satisfaction of the people but also the urgent requirement of cultivating high-quality professionals with safety responsibility consciousness and safety behavior ability. Starting from the history of safety culture construction, this paper reviews and summarizes the course of safety culture construction in colleges and universities, analyzes the present situation of safety culture construction in colleges and universities, and takes the safety construction theory as the guide. This paper introduces an automatic extraction technology of Internet map POI data. The organization form of Html webpage content, the automatic analysis, and the extraction of POI are realized by programming. The experimental results show that the address standardization method proposed in this paper has high accuracy of address standardization, and the weighted multiattribute similarity POI matching method can also effectively update the increment of POI data.